(untitled) (GAIMS Journal of Medical Sciences, 2025)
Background: Antenatal care is crucial for reducing maternal and neonatal mortality by ensuring the health of both the mother and fetus during pregnancy. Effective ANC services can significantly impact pregnancy outcomes, especially in rural settings where healthcare access is often limited. Our study aimed to evaluate the antenatal care services provided at a rural health center in Gujarat, India, focusing on early pregnancy registration rates, anemia prevalence, compliance with Iron-Folic Acid (IFA) supplementation, and delivery outcomes. Materials and Methods: A cross-sectional, record-based study was conducted at Jetalpur, PHC, a Rural Health Training Centre under Narendra Modi Medical College, Ahmedabad, using Technology for Community Health Operations (TeCHO+). Data from 387 pregnant women registered between April 2021 and March 2023 were analyzed using descriptive and comparative statistics. Results: The study found a high early pregnancy registration rate of 89.66%, reflecting effective community outreach. However, anemia prevalence was significant at 78.87%, and only 3.79% of women completed the full course of IFA supplementation. Normal deliveries accounted for 71.21% of births, while Cesarean sections were 28.78%. Preterm births were recorded at 28.79%. Conclusions: The study underscores the need for enhanced health strategies in rural areas to address anemia and improve compliance with ANC protocols. Continued efforts are essential to strengthen maternal health services and reduce disparities in rural healthcare.